Enhancing Continuity of Emergency Care through Interdisciplinary Coordination among EMS, Nursing, and Pharmacy in General Hospitals - Mohammed Shayi Alqhtani, Mubarak Muhammad Bijad Alqahtani, Falh Falah Mesfer Alqahtani, Salem Eid Mohammed Al Aljrw, Mohammed Abdulaziz Alhothely; Khalid lafi alosaimi, Bander Turki Almutari, May Dhwahi Almutairi, Yazi Mowafiq Alanazi and Abdulaziz Raja Hudaib Al-Otaibi (Journal of International Crisis and Risk Communication Research, 2024)
Improving the continuity of emergency care for patients admitted to general hospitals requires effective interdisciplinary coordination among emergency medical services (EMS), nursing, and pharmacy. This coordination helps provide timely treatment and preventive measures, reduces avoidable hospital admissions, and enhances medication safety. The objective of this study is to identify the current state of emergency care continuity, clarify the roles and interactions of these three stakeholders, highlight barriers to coordination, and review interventions that have shown promise in general hospital settings. A systematic discussion of these topics can inform the design and implementation of interdisciplinary coordination initiatives at general hospitals. Emergency care continuity refers to the transfer of care information and responsibility among different stakeholders throughout the emergency care process (Al-Salloum et al., 2020). Emergency care involves multiple stakeholders, long care processes, and numerous transitions, making continuity particularly challenging. Yet these characteristics are often overlooked in general hospitals, where significant continuity gaps persist between EMS and nursing, as well as between nursing and pharmacy. Effective collaboration among EMS, nursing, and pharmacy has significant potential to close these gaps.